FORMULASI DAN UJI STABILITAS FISIK EMULGEL TABIR SURYA EKSTRAK ETANOL KULIT BUAH JERUK NIPIS (Citrus aurantifolia) MENGGUNAKAN VARIASI NILAI HLB EMULGATOR - rina widiastuti (JURNAL ILMU KESEHATAN BHAKTI SETYA MEDIKA, 2020)
Lime peel (Citrus aurantifolia) contains flavonoid compounds and vitamin C which can be used as block to free radicals, so it has the potential to be formulated into sunscreen preparations in the form of emulgel. Emulgel consists of two systems namely the gel system and emulsion system. The physical stability of the emulgel is affected by the emulgator. This study aims to determine the effect of HLB emulgator tween 80 and span 80 variations in the physical stability of the emulgel. Therefore in this study used variations in the value of HLB emulgator tween 80 and span 80 with a comparison that is F1: HLB 10 (2,7 : 2,3); F2: HLB 11 (3,1 : 1,9); dan F3: HLB 12 (3,6 : 1,4).The physical stability test of the emulgel was carried out in two conditions namely before and after storage was accelerated by the freeze thaw period for 5 cycles with the test parameters including organoleptic, homogeneity, type emulsion, pH, adhesion, dispersion. The data obtained were then analysed statistically in a sensitivity level of 95 with One Way Anova test. Based on these results indicate that variations in the value of HLB emulgator tween 80 and span 80 affect the value of dispersion and adhesion with the value of p-value 0,000 < 0,05. Based on descriptive analysis shows that all formulas are homogeneously mixed, have emulsion type o/w and pH 6. The HLB 12 emulgator tween 80 and span 80 (3,6 : 1,4)values provide better physical stability, with a texture that is not too sticky when applied, feels cold skin, and has the most widespread distribution.